Saudi Arabia : 2019 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
Reforms are starting to yield positive results. Oil prices and production have been volatile, and uncertainties in the global oil market continue. Promoting non-oil growth and creating jobs for Saudi nationals remain key challenges. Non-oil growth is expected to strengthen further this year and over the medium term. Risks to the growth outlook are broadly balanced.